THE HISTORY OF THE TANBUR: FORMATION, DEVELOPMENT, AND LEGACY - Zufarov Abror Mahamad-Sadikovich (Bright Mind Publishing, 2025)
This article discusses the tanbur, one of the oldest musical instruments. It presents the history of its evolution, various forms, and provides information about the musicians and researchers who have performed and studied the tanbur, as well as the master craftsmen and teachers who dedicated their lives to its creation and enhancement.
Keywords: Tanbur, sato, instrumental art, Usmon Zufarov, Turgun Alimatov, national art, music, Shashmaqom, parda, history